Annotated list of fishes caught by the R/V ARQUIPÉLAGO off the Cape Verde archipelago. - Menezes, Gui M. (2008)
A prospective survey was carried out in October - November of 2000, in the Cape Verde archipelago, by the R/V ARQUIPÉLAGO. The main objective was to determine the species composition and relative abundance of the demersal fish resources living in the waters of the Cape Verde archipelago. A list of fishes caught with bottom longline during the survey is presented in this document, along with information about the area, depth limits and the relative abundance of the species in the catches. Ninety-seven different species from 49 families were identified from 20 long-line sets. To our knowledge, the following 12 species were recorded for the first time from the waters of Cape Verde islands: Etmopterus princeps, Etmopterus pusillus, Gymnothorax maderensis, Myroconger compressus, Laemonema robustum, Beryx splendens, Scorpaena elongata, Serranus atricauda, Taractes rubescens, Taracthichthys longipinnis, Pagrus africanus and Cathidermis sufflamen. The species Laemonema robustum, were new to the CLOFETA area.